ARCHEOZOOLOGICAL STUDIES OF VERKHNENOYBERSKOYE 1 SETTLEMENT - Zilivinskaa, Emma Davidovna; Magkova, Ulia Akovlevna (History, Archeology and Ethnography of the Caucasus, 2025)
In 2022 and 2023, rescue excavations were conducted at the 17th–19th-century settlement of Verkhnenoyberskoye 1 in the Gudermes District of the Chechen Republic. The excavation area encompassed the settlement’s agricultural zone rather than its residential core, revealing seasonal structures used for processing agricultural products, furnace chambers, and clay extraction pits. This paper presents the findings of an archeozoological analysis of materials recovered from these excavations. The primary objective is to introduce the results of the archeozoological collection from Verkhnenoyberskoye 1 into scholarly discourse. The study employs contemporary methodologies developed at the Institute of Archaeology of the Russian Academy of Sciences to investigate the roles of hunting and animal husbandry in the settlement’s economy. The archeozoological assemblage comprises 11,881 bone fragments, with fish and bird remains being scarce and wild mammal bones rare. Domestic ungulates predominate, with small ruminants constituting the largest proportion, followed by cattle, with fewer horse remains and minimal pig bones. Beef was the primary meat consumed, and the slaughter of young cattle and small ruminants, peaking at approximately two years of age, indicates a sustainable production system. Cattle were primarily utilized for meat and dairy, with an emphasis on milk production, while small ruminants were raised for wool, milk, meat, and hides. Domestic animal bones were also repurposed for simple household tools. Notably, the assemblage includes 39 large dog skeleton fragments and 83 scattered dog bones, suggesting significant dog mortality. Two hypotheses are proposed: death due to natural causes or as a result of shifts in religious practices.
Keywords: modern era; Chechen Republic; archeology; settlement; archeozoological study; mass burial of dogs; husbandry; animal protein sources; bone household tools